Diagnosis, Hematologic Profile, and Treatment of Cystoisosporiasis in Domestic Dog - Fadila, Kurnia Asyafia; Kusumarini, Shelly (Universitas Airlangga, 2024)
Cystoisosporiasis infection is caused by Cystoisospora spp. or Isospora spp. in dogs. Cystoisospora spp. are protozoa ordo Eucoccidiorida. Cystoisosporiasis is considered more risky in puppies. Clinical manifestations of cystoisosporiasis tend to be watery diarrhea to melena in puppies which can also be concurrent with vomiting, and tenesmus, whereas in adult dogs known as symptomatic. A female domestic dog, aged >1 yo was kept indoors and had not been vaccinated or anthelmintic drugs. The dog has changed in the consistency of slightly soft feces with a frequency of defecation 1–2 times a day. Diagnose performed using microscopic fecal examination with the floating method found the presence of Cystoisospora spp. oocysts, followed by the calculation of oocysts per gram (OPG) using a two-chamber McMaster to determine the degree of Cystoisospora spp. infection. Blood examination showed leukocytosis, granulocytosis, and hypochromic anemia. The treatment was administered of 15 mg/kg BW sulfadiazine orally every 12 hours for 7 days, 14 mg/kg BW metronidazole every 12 hours for 7 days, and 300 mg Hemafort® every 24 hours for 7 days. After 7 days of treatment, we reported normal fecal consistency and negative parasitic manifestation. Prevention was done by paying attention to treatment, immediately identifying the presence of oocysts, educating owners to avoid animal distress, and maintaining a good hygiene environment.